Treatment outcome of radiotherapy alone versus radiochemotherapy in IE/IIE extranodal nasal-type natural killer/T cell lymphoma: a meta-analysis. - Tianxia Deng (Public Library of Science (PLoS), 2014)
Background Previous studies have revealed conflicting findings concerning the efficacy of radiotherapy (RT) and radiochemotherapy (RCT) in IE/IIE extranodal nasal-type natural killer/T cell lymphoma (ENKTL). In this study, we conducted a comprehensive meta-analysis to address this issue. Methods We systematically searched PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), EmBase, BISOS, Clinical Trials and some Chinese databases for relevant studies, and 2 prospective and 15 retrospective studies involving a total of 1595 patients met our inclusion criteria. Results The meta-analysis showed no significant differences in complete remission (CR) [odds ratio (OR) 0.85, 95% confidence interval (CI) 0.42-1.72, p = 0.65], 5-year overall survival (OS) [hazard ratio (HR) 1.11, 95% CI 0.85-1.45, p = 0.43] and 5-year progression free survival (PFS) (HR 1.07, 95% CI 0.75-1.53, p = 0.70) in patients who received RT versus RCT. Furthermore, the addition of CT decreased neither systemic failure (SL) (OR 0.75, 95% CI 0.47-1.21, p = 0.24) nor locoregional failure (LF) (OR 1.17, 95% CI 0.68-2.01, p = 0. 57). Conclusions RCT did not have an obvious advantage over RT for treating IE/IIE ENKTL.